Efektifitas Cadre Refreshment dalam peningkatan peran kader dalam penanggulangan TBC di Kabupaten Sumenep - Zetiawan Trisno; Lukman Nurhakim (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2023)
Tuberculosis is a deadly infectious disease caused by the bacterium Mycobacterium tuberculosis. Indonesia is currently in the second-highest position in the world. Efforts to break the chain of TB in the community require capacity building for cadres as the spearhead in finding and assisting people with TB. The involvement of cadres in TB control programs can be realized through the provision of training. The purpose of cadre refreshment training is to provide understanding and skills for cadres in carrying out case-finding activities and treatment assistance for TB patients. The method used in this activity consists of teaching, simulation, field practice, and continuous evaluation. This training was attended by 45 cadres from 18 areas of the YABHYSA SSR intervention health center Sumenep. Cadre participants consist of 85% women and 15% men and most of them are at the productive age of 89%.